AI INTEGRATION IN AUTONOMOUS ENGLISH LEARNING: EVOLVING OPPORTUNITIES AND DETERMINED CHALLENGES - Fitriati, Rahima; Mafruudloh, Naajihah; Tasaufi, Bila Nastiti; Zamzami, Muhammad Rizal Akbar; Rahmawati, Zurriat Nyndia (FKIP - Universitas Tanjungpura, 2026)
The improvement of Artificial Intelligence (AI) offers abundant profits for educational practices, especially in English learning for university students. This paper observes the application of AI tools by students in preparing presentation tasks. Descriptive qualitative research using a questionnaire is used as a research methodology. Data were collected from 51 English for Specific Purposes (ESP) students majoring in Law and Informatics Engineering. A questionnaire consisting of Likert-scale and open-ended items was utilised to discover students’ perception of benefits, challenges, as well as their critical concerns about using AI. Quantitative data from Likert-scale items were analysed using descriptive statistics, while qualitative responses were analysed to discover key benefits, challenges, and ethical concerns related to AI-assisted autonomous English learning. The findings reveal that students frequently used several AI tools, such as ChatGPT, Canva AI, and Grammarly, to support autonomous learning, such as vocabulary development, grammar mastery, and speaking practice. However, limitations appeared, including imprecise outputs, lesser human interaction, potential overreliance on AI, and anxieties related to data privacy and limited consideration of AI instruments. These challenges highlight the need for reinforced digital literacy as well as clear guidance and instruction from the lecturer to preserve meaningful communication and appropriate use of AI tools. The study hints that while AI effectively enhances autonomous English learning, its implementation must be supervised by educators to ensure responsible usage, promote critical thinking, and preserve the human interaction aspects of language education.